Time management and translation method in translating a scientific article: A case study on a professional translator - Amsaldi Wahyu Kristian Sinulingga; Rudy Sofyan; Umar Mono (UNIB Press, 2023)
As an activity of transferring a message from a source text to a target text, translation certainly involves several processes. Different processes require certain amount of time allocation depending on the translator’s cognitive load. Studying translation process is essential to reveal what actually happened while a translator was doing his/her tasks, contributing to a better translation product. This study aimed at finding out the time management and the translation method in translating a scientific article by a professional translator. The scientific article is composed of more than five thousand words; thus, the researcher reduced the limit of the words to one thousand words to avoid the technical problems. This qualitative study used a case study as the research method. The participant of this research was a professional translator from the Association of Indonesian Translator (HPI). The data were collected using a keyboard logging program (Translog-II) and a screen recording tool (OBS Studio). Based on the data analysis it was found that the professional translator (i) distributed more time in the drafting stage; and (ii) applied the linear and inline methods during the translation process. It was found that the professional translator focused translating on word by word, phrase by phrase, and paragraph by paragraph. It is concluded that the activities in each stage of translation process contributes to the result of translation.